Evaluating of Red Blood Cell Distribution Width, Comorbidities and Electrocardiographic Ratios as Predictors of Prognosis in Patients with Pulmonary Hypertension - Baltazares-Lipp, Mario E. (Diagnostics (Basel), 2021)
Pulmonary hypertension is a rare condition that impairs patients’ quality of life and life expectancy. The development of noninvasive instruments may help elucidate the prognosis of this cardiorespiratory disease. We aimed to evaluate the utility of routinely performed noninvasive test results as prognostic markers in patients with pulmonary hypertension. We enrolled 198 patients with mean pulmonary artery pressure >25 mmHg measured at cardiac catheterisation or echocardiographic pulmonary artery systolic pressure > 40 mmHg and tricuspid regurgitation Vmax >2.9 m/s, and clinical information regarding management and follow-up studies from the date of diagnosis. Multivariate analysis revealed that female sex [HR: 0.21, (95% CI: 0.07–0.64); p = 0.006], the presence of collagenopathies [HR: 8.63, (95% CI: 2.38–31.32); p = 0.001], an increased red blood cell distribution width [HR: 1.25, (95% CI: 1.04–1.49); p = 0.017] and an increased electrocardiographic P axis (P°)/T axis (T°) ratio [HR: 0.93, (95% CI: 0.88–0.98); p = 0.009] were severity-associated factors, while older age [HR: 1.57, (95% CI: 1.04–1.28); p = 0.006], an increased QRS axis (QRS°)/T° ratio [HR: 1.21, (95% CI: 1.09–1.34); p < 0.001], forced expiratory volume in 1 s [HR: 0.94, (95% CI: 0.91–0.98); p = 0.01] and haematocrit [HR: 0.93, (95% CI: 0.87–0.99); p = 0.04] were mortality-associated factors. Our results support the importance of red blood cell distribution width, electrocardiographic ratios and collagenopathies for assessing pulmonary hypertension prognosis.